Penggunaan Qris Sebagai Sistem Cashless Dalam Meningkatkan Efisiensi Transaksi Umkm di UPN “Veteran” Jawa Timur - Arief Bachtiar; Mohhammad Wesla Dhifayana Sukirman; Natasha Claudia Ambarita; Diva Delia Rossa Nicolas; Vinda Cendrawati; Wardah Fadiah Salsabila (Universitas Kristen Indonesia Toraja, 2024)
The era of the digital economy, known as the fourth industrial revolution, has brought significant technological advances, especially in the field of digital payment systems. Although this system has advantages and disadvantages, this system is generally superior to other payment systems. It is importat to note that the presence of a digital payment system does not mean eliminating physical cash. Carrying out research regarding the use of QRIS for MSMEs in the UPN “Veteran” East Jawa canteen uses a quantitative apporach to collect and analyze data related to the efficiency of MSME transactions in the UPN Veteran East Jawa canteen using QRIS as an electronic payment method. The sample for this research was taken randomly from MSMEs in the UPN “Veteran” East Jawa canteen. Directly from the knowledge of business actors to the obstacles faced, this discussion chapter discusses in detail the key findings that emerged during the research process.1. business Actors’ Knowledge of Qris. 2. Benefits of QRIS for Business Actors. 3. Barriers to Business Actors in Using QRIS. 4. Practical Implications and Recomendations. 5.Ease and Speed of Transactions. 6. Cheaper Transaction Fees. 7. Improved Transaction Records. 8. Inflation Control and Monitoring of Goods Prices